Towards perfect completeness remembering Lutosławski - Tomaszewski, Mieczysław (Interdisciplinary Studies in Musicology, 2018)
The text is in its character a statement by a “witness to an era”. It is an attempt at describing Lutoslawski’s artistic path and his culture-forming activity from the perspective of an evolution within a concrete historical and political situation. This aesthetic evolution is evidenced in the composer’s utterances: significant interviews and private, confessional notes. They outline his creative path from the impact of Chopin as the emotional arche, through subsequent phases and breakthroughs: from academic aesthetics based on the Hanslick paradigm, through socialist-realist indoctrination and uncritical fascination with the avant-garde, to a gradual crystallisation of his own idiom. Eventually, this entirely own idiom, marked with a lyrical opening, consists in a return to everlasting values, expressly defined by the composer: the truth and the beauty of a work of art.